Nocturnal pruritus and sleep disturbance associated with dermatologic disorders in adult patients - Indrashis Podder, MD; Himel Mondal, MD; George Kroumpouzos, MD, PhD, FAAD (Wolters Kluwer, 2021)
Nocturnal pruritus (NP) is a relatively common reason for dermatologic consultation. Its pathophysiology is partially understood. Skin conditions such as atopic dermatitis, psoriasis, urticaria, and prurigo nodularis are well-described causes of NP. The most distressing sequela of NP is sleep deficit, which can lead to physical and mental disturbances (e.g., daytime somnolence and fatigue) and negative emotional states that profoundly affect quality of life. However, this aspect of NP is often overlooked by dermatologists. It is essential to assess sleep quality in such patients and adopt appropriate measures to arrest the problem at an early stage. We conducted an evidence-based literature review to highlight the pathogenetic mechanisms of NP, identify dermatologic etiologies, and explore methods that have been used to assess the quality of sleep. Furthermore, we performed a systematic review of studies on sleep disturbance relevant to NP in patients with dermatologic conditions. Finally, we discuss the evidence on treatment options for NP and indicate therapies that may target both NP and sleep disturbance.